Adjustments of capital account restrictions and exchange rate regimes in East Asia - Naoyuki Yoshino; Sahoko Kaji; Tamon Asonuma (Asian Development Bank Institute (ADBI), 2015)
This paper discusses adjustments of capital account restrictions and exchange rate regimes in East Asia. Monetary authorities have two options for these adjustments: gradual adjustments or rapid adjustments. We analyze the costs and benefits for both adjustment options in each area, i.e., capital account restrictions and exchange rate regime. The paper provides prominent country cases for each adjustment option to emphasize the benefits for policymakers. We then propose four transition policy options for East Asian countries aiming to relax capital account restrictions and increase flexibility in exchange rates from fixed regimes with capital account controls.
Keywords: F33; F41; F42; 330; exchange rate transition; east asia; capital account controls; exchange rate transition policies